Replacement of administration set for arterial catheter 4 days versus 7 days - Daud, Azlina (2017)
Introduction The prevalence of administration sets (AS) used for peripheral arterial catheter (PAC) of critically ill patients is not known, however, approximately six million PACs were placed yearly in the USA (Gowardman et al., 2010) which can estimate the use of AS for PAC to be at least the same number. Most recent research has investigated the prolonged use of AS associated with the incidence of CVC related BSIs with no recent studies on replacement of AS for PAC. The objective of this study is to rigorously test the efficacy or equivalence of AS replacement for PAC at 4 days versus 7 days. Patients were randomised into two groups; the control group had the PAC-AS replaced every four days and the experimental group had the PAC-AS replaced every seventh days. Results 100 patients were randomised, 50 in the 4-day group and 50 in the 7-day group. Of the 50 patients in each group, 90% in the 4-day group and 60% in the 7-day group had the AS changed for the first time. There was zero percentage of CRBSI of the AS replacement for PAC at 4 days and 7 days. Conclusion Information derived from this study provides clinicians the need for high quality evidence on the impact of extended, AS use for PAC beyond 4 days in the form of RCT is required. There is limited evidence to suggest changing AS at 96 hours or more effects the risk of PAC-BSI among critically ill patients, indicating that large randomised trials of high quality are needed.